A Scheduling Tool for Bridging the Gap Between Aircraft Design and Aircraft Manufacturing - Pralet, Cédric; Roussel, Stéphanie; Polacsek, Thomas; Bouissière, François; Cuiller, Claude; Dereux, Pierre-Eric; Kersuzan, Stéphane; Lelay, Marc (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
For aircraft manufacturers, the market demand in the nowadays aeronautical industry requires a high reactivity between teams in charge of the design of the aircraft and teams in charge of its production system. One way to increase this reactivity is to help the design architects understand the way the aircraft is produced together with the bottlenecks in the manufacturing process, and to help them evaluate the impact of a design modification on the production system. This paper addresses these two needs. We formally describe the scheduling problem considered, the algorithmic approaches developed, the implemented tool, and results obtained on data from a real production line of the Airbus A320 aircraft family.